Identification of Adenosquamous Carcinoma as a Rare Aggressive HER2-negative Subgroup of Esophageal/Gastroesophageal Junction Adenocarcinoma. (February 2019) - Jin, Zhaohui; Holubek, Marie; Sukov, William R.; Sattler, Christopher A.; Wiktor, Anne E.; Jenkins, Robert B.; Wu, Tsung-Teh; Yoon, Harry H.
Abstract : Background: Our purpose was to evaluate the prognostic impact of pathologically confirmed esophageal adenosquamous carcinoma (ASC) and its association with HER2 status and clinicopathologic characteristics. Methods: Among 796 patients with esophageal or gastroesophageal junction adenocarcinoma who underwent curative resection, surgical pathology reports were reviewed, and suspected ASC was confirmed utilizing p63 and CK5/6 immunostaining. HER2 status was determined using immunohistochemistry and fluorescence in situ hybridization. Cox models were used to assess the impact of ASC on disease-specific survival and overall survival. Results: Overall, 2.0% (16/796) of patients had esophageal ASC, mostly demonstrating a close intermingling of squamous and adenocarcinoma cells within the same tumor. The percentage of squamous versus adenocarcinoma cells in the primary was generally recapitulated in nodal metastases, and intrapatient internodal heterogeneity was uncommon. Patients with esophageal ASC were statistically significantly more likely to be female (vs. male), have normal (vs. excess) body mass index, and harbor HER2-negative (vs. positive) tumors, as compared with patients with adenocarcinoma only. No ASC tumor was HER2-positive as compared with 16% of adenocarcinoma only tumors ( P =0.018). Compared with patients with adenocarcinoma only, those with ASC demonstrated profoundly worse disease-specific survival (5-year event-free rate, 34% vs. 6%; multivariate hazard ratio, 2.87 [95% confidence interval, 1.59-4.76]; P =0.0010) and overall survival ( P =0.0027) that was independent of known prognostic factors and HER2 status. Conclusion: ASC identifies a rare aggressive HER2-negative subgroup of esophageal/gastroesophageal junction adenocarcinoma. Abstract : Supplemental Digital Content is available in the text.